Management of adverse effects of new monoclonal antibody treatments in acute lymphoblastic leukemia - Conde-Royo, Diego (Drugs Context, 2020)
Therapeutic options for relapsed/refractory B-cell acute lymphoblastic leukemia have evolved in the past few years. The FDA has approved three novel therapies for this disease: inotuzumab ozogamicin (an anti-CD22 antibody–drug conjugate), blinatumomab (a bispecific T-cell engager), and chimeric antigen receptor T-cell therapy. Although these novel immunotherapies have revolutionized the therapeutic landscape, it is important to understand the crucial aspects of administration, especially toxicity. In this article, we review the unique toxicities and adverse effects of blinatumomab and inotuzumab ozogamicin and provide recommendations for prevention of adverse effects as well as the management options for each medication.